Constructing clienthood in social work and human services : interaction, identities, and practices - Hall, Christopher, 1948- (Jessica Kingsley Publishers, 2003)
This innovative book explores social work as a series of encounters - between clients and social workers, social workers, their colleagues and other professionals, and more widely between citizens and the state. Providing a variety of social constructionist perspectives on the idea of the 'client', it presents in-depth discussion of the roles, language and contexts of meetings between social workers and their clients. International contributors present discussion on categorization, analyzing 'roles', and reflexive practice. Drawing data from a variety of sources, including legislation, client.